Effectiveness and underlying mechanisms of a group-based cognitive behavioural therapy-based indicative prevention program for children with elevated anxiety levels - van Starrenburg, Manon LA (BioMed Central, 2013)
BACKGROUND: Anxiety is a problem for many children, particularly because of its negative consequences not only on the wellbeing of the child, but also on society. Adequate prevention and treatment might be the key in tackling this problem. Cognitive behavioural therapy (CBT) has been found effective for treating anxiety disorders. “Coping Cat” is one of the few evidence-based CBT programs designed to treat anxiety symptoms in children. The main aim of this project is to conduct a Randomized Controlled Trial (RCT) to evaluate the effectiveness of a Dutch version of Coping Cat as an indicative group-based prevention program. The second aim is to gain insight into the mechanisms underlying its effectiveness. METHODS/DESIGN: Coping Cat will be tested in Dutch primary school children grades five through eight (ages 7 to 13) with elevated levels of anxiety. This RCT has two conditions: 130 children will be randomly assigned to the experimental (N=65, Coping Cat) and control groups (N=65, no program). All children and their mothers will be asked to complete baseline, post intervention, and 3-month follow-up assessments. In addition, children in both the experimental and control group will be asked to complete 12 weekly questionnaires matched to the treatment sessions. Main outcome measure will be the child’s anxiety symptoms level (SCAS). Four potential mediators will be examined, namely active coping, positive cognitive restructuring, self efficacy and cognitions about ones coping ability (from now on coping cognitions). DISCUSSION: It is hypothesized that children in the experimental condition will experience reduced levels of anxiety in comparison with the control group. Further, active coping, positive cognitive restructuring, and coping cognitions are expected to mediate program effectiveness. If Coping Cat proves effective as a prevention program and working mechanisms can be found, this group-based approach might lead to the development of a cost-effective program suitable for prevention purposes that would be easily implemented on a large scale. TRIAL REGISTRATION: Nederlands Trial Register NTR3818.